Optimization of RUSITEC model adaptations for in vitro simulation of subacute ruminal acidosis and evaluation of Saccharomyces cerevisiae supplementation on microbial fermentation and stability - Petri, Renee Maxine; Antlinger, Birgit; Khol, Lorenz Johannes; Gruber, Christina; Kesselring, Jutta Cordula (Frontiers in Animal Science, 2025)
There is a growing need for alternative research models to reduce or replace animal use in feed and feed additive testing. In vitro model development could provide value added data in the assessment of feed additives for microbial modulation in cattle where animal variation in intake can impact results. This study aimed to refine and evaluate the in vitro model of subacute ruminal acidosis (SARA) and assess how variations in buffer and feed additive supplementation could influence microbial fermentation and community composition. Using the rumen simulation technique (RUSITEC) with a SARA model, buffer dilution and feed additive supplementation were compared for their influence on microbial fermentation and community composition. Results showed that buffer dilution, combined with dietary changes, effectively induced SARA in vitro, with a significant impact on ruminal pH and fermentation parameters. Acetate production and pH were lower in reactors supplemented with Saccharomyces cerevisiae (AY), especially under low buffering conditions, suggesting AY’s potential to mitigate ruminal dysbiosis. Microbial protein and protozoa abundance also changed in response to dietary and buffer adjustments. The results of this study support the use of in vitro models for more controlled, reproducible testing of feed additives, with potential applications in improving nutritional interventions and rumen microbial stability.